Prevalencia de riesgos ergonómicos en el personal administrativo del Gobierno Autónomo Descentralizado del cantón Chone - Saltos Moreira, Karla Alexandra (2025)
This research aimed to determine the prevalence of ergonomic risks among administrative staff at the Decentralized Autonomous Government of Chone canton, in order to establish preventive measures that enhance their health and workplace well-being. The study was carried out in three phases, aligned with the research procedures. In the first phase, a literature review and analysis of regulations related to ergonomic conditions were conducted. Semi-structured interviews were carried out with employees from different departments, and direct observation of workstations was performed, focusing on posture, equipment, and furniture. In the second phase, field instruments were applied based on the dimensions of the study variable and a Likert scale. These instruments were validated through documentary analysis. The interview was directed to the Occupational Health Department, and the survey was applied to staff members of the local government. The findings revealed several ergonomic risks, including poor practices such as incorrect posture and repetitive movements, as well as exposure to unfavorable environmental conditions like stale air, disturbing noise, and cleaning products. In response, the third phase involved the design of an ergonomic safety plan to address and strengthen the identified areas of concern. In conclusion, the study highlights the importance of creating a safer and more comfortable work environment that fosters both institutional productivity and employee well-being.